Implementasi Metode Ummi dalam Meningkatkan Literasi Arab Dasar melalui Pembelajaran Al-Qur'an Siswa - Siswanto, Wawan; Nuryana, Nuryana; Hidayat, Ade (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to describe the implementation of the Ummi Method in improving basic Arabic literacy through Qur'anic learning among seventh-grade students at an Islamic junior high school. A descriptive qualitative approach was employed. Data were collected through participant observation, in-depth interviews, and a documentation study. The primary data sources were four key informants selected purposively, namely the school principal, two certified Ummi teachers, and the Ummi program coordinator, complemented by secondary data obtained from oral reading tests and brief interviews with twelve seventh-grade students representing high, moderate, and low reading-ability groups, as well as school documents including curriculum records, lesson plans, student progress reports, and teacher certification files. Data were analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing/verification, with credibility ensured through source and method triangulation. The findings show that the Ummi Method was implemented through three structured stages: classical instruction, individual assessment, and guided recitation. The method effectively improved students' hijaiyah letter recognition from an average of 45% to 87%, harakat comprehension from 38% to 82%, and reading fluency from 30% to 79% over one semester. Supporting factors included certified teacher competence, institutional support, and curricular integration, while inhibiting factors included students' heterogeneous initial abilities and limited instructional time. This study concludes that the systematic implementation of the Ummi Method significantly enhances students' basic Arabic literacy and recommends its wider adoption in Islamic junior high schools across Indonesia.